Friction and wear behavior of Ni-based solid-lubricating composites at high temperature in a vacuum environment. (15th May 2017) - Cheng, Jun; Zhen, Jinming; Zhu, Shengyu; Yang, Jun; Ma, Jiqiang; Li, Wensheng; Liu, Weimin
Abstract: In this paper, the effect of the complex condition with high temperature and vacuum on the tribological properties of NiCrMoAl-Ag-CaF2 /BaF2 solid-lubricating composite has been investigated. It presents that this composite displays the excellent tribological properties in vacuum than in air from room temperature to 800 °C. In vacuum, the friction coefficients are around or below 0.20 and superior to that in air. Besides, the wear rates in vacuum are at least one order of magnitude lower than those tested in air. They can be divided into three stages with the temperature (10 − 7 mm 3 /Nm at room temperature and 200 °C, 10 − 6 mm 3 /Nm between 400 and 600 °C, and 10 − 5 mm 3 /Nm at 800 °C). Also, the surface oxidation behavior and the lubrication characteristics of solid lubricants (Ag and fluorides) in vacuum are clarified and related to the tribological properties. Graphical abstract: Highlights: The Ni-based composite exhibits excellent tribological properties at high temperature in a vacuum. The lubrication lifetime and mechanisms of Ag and CaF2 /BaF2 are clarified in vacuum. Surface oxidation is detrimental to the wear-resistance of the composite.